Selection of Elite Genotypes of Coffee arabica L. to Produce Specialty Coffees - Malta, Marcelo Ribeiro; Oliveira, Antonio Carlos Baiao; Liska, Gilberto Rodrigues; Carvalho, Gladyston Rodrigues; Pereira, Antonio Alves; Silva, Ackson Dimas; Alvaro, Laisa Nayara; Mota, Diego Menez (Frontiers in Sustainable Food Systems, 2021)
This study aimed to determine the beverage quality and sensory profile of Arabica coffee genotype elite groups submitted to wet processing. Coffea arabica L. elite genotypes, which were divided into groups according to their genealogical origin: Bourbon Group, Paraíso Germplasm Group, and Group Resistant to Rust. Coffees were sent to wet processing to obtain pulped coffee. After processing and drying the coffees were subjected to sensory analysis according to the Association of Special Coffees. The data were submitted to chemometric analysis, PCA and PLS-DA, to characterize and discriminate the genealogical groups. The PCA identified the trends of most of the elite genotypes evaluated with respect to virtually all sensory attributes. The results of the PLS-DA model showed the variables that most influenced the classification of genealogical groups. The Coffea arabica elite genotypes evaluated have the potential to produce special coffees, with emphasis on the genotypes Paraíso 2, H493-1-2-10 and UFV-7158.